1994
DOI: 10.1111/j.1600-051x.1994.tb00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the relationship between changes in radiographic bone height and probing attachment

Abstract: The aim of this investigation was to determine the relationship between loss of radiographic crestal bone height and probing attachment loss. As part of this aim, we are introducing a new method for determination of a threshold for significant probing attachment loss which takes into account the error contributed by alteration in tissue tone. 57 adults with established periodontitis were selected. Radiographs were taken using the Rinn alignment system. Crestal change was determined from bone height measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 10 publications
0
25
0
3
Order By: Relevance
“…In most cases, assessment of periodontal disease status is now performed using periodontal probing (with clinical attachment-loss measurements made in relation to a fixed anatomical landmark, usually the CEJ) and/or alveolar bone levels from intraoral radiographs. Both of these techniques are vulnerable to errors [12, 13, 14]. While periodontal probing remains the gold standard for periodontal assessment, it has several limitations regarding reproducibility and sensitivity, depending on the degree of edema and probing technique (for example, probing force, angle of the probe, size of the probe and probe calibration [that can differ from one brand to another]), making the detection of small changes difficult [15].…”
Section: Radiographic Measurement Of Alveolar Crest Heightmentioning
confidence: 99%
“…In most cases, assessment of periodontal disease status is now performed using periodontal probing (with clinical attachment-loss measurements made in relation to a fixed anatomical landmark, usually the CEJ) and/or alveolar bone levels from intraoral radiographs. Both of these techniques are vulnerable to errors [12, 13, 14]. While periodontal probing remains the gold standard for periodontal assessment, it has several limitations regarding reproducibility and sensitivity, depending on the degree of edema and probing technique (for example, probing force, angle of the probe, size of the probe and probe calibration [that can differ from one brand to another]), making the detection of small changes difficult [15].…”
Section: Radiographic Measurement Of Alveolar Crest Heightmentioning
confidence: 99%
“…Radiographic measurement of alveolar bone is an accurate method for assessment of periodontitis [11][12][13] and compares favorably with clinical measures of periodontitis. 14 The panoramic radiograph can be performed in a few minutes in relative patient comfort compared with 20 to 30 minutes for a complete clinical oral evaluation. Interestingly, Ravon et al have shown a high degree of correlation between carotid artery calcifications and CP severity, both determined from the same panoramic radiograph.…”
Section: Engebretson Et Al Periodontitis and Carotid Plaque 563mentioning
confidence: 99%
“…14 However, to date, radiographs have not been used to assess CP in research studies of subclinical atherosclerosis. The present crosssectional study was undertaken to measure CP radiographically and to determine the association with carotid artery plaque in a stroke-free community-based cohort.…”
mentioning
confidence: 99%
“…Jeffcoat 2 reported a strong concordance between presence or absence of probing attachment loss and bone loss. In contrast to these reports, Hausmann et al 3 and Machtei et al 4 found only very weak relationships between changes in radiographic bone height and probing attachment level.…”
mentioning
confidence: 92%